The Heterogeneous Impact of Short-Time Work: From Saved Jobs to Windfall Effects - Pierre Cahuc; Francis Kramarz; Sandra Nevoux (Institute of Labor Economics (IZA), 2021)
To understand which firms take-up short-time work and which workers they enroll in this program, we provide a model which shows that short-time work may save jobs in firms hit by strong negative revenue shocks, but not in less severely-hit firms, where hours worked are reduced, without saving jobs. Using detailed data on the administration of the program covering the universe of French establishments in the 2008-2009 Great Recession, we find that short-time work did indeed save jobs and increase hours of work in firms faced with large negative shocks. These firms have been able to recover rapidly in the aftermath of the Recession thanks to short-time work. We also provide evidence of large windfall effects which significantly increased the cost of the policy per job saved; yet we also find that short-time work remains more cost-efficient at saving jobs than wage subsidies.
Keywords: E24; J22; J65; 330; short-time work; employment; hours of work